Patterns of exchange of forensic DNA data in the European Union through the Prüm system. Issue 4 (July 2017) - Santos, Filipe; Machado, Helena
Abstract: This paper presents a study of the 5-year operation (2011–2015) of the transnational exchange of forensic DNA data between Member States of the European Union (EU) for the purpose of combating cross-border crime and terrorism within the so-called Prüm system. This first systematisation of the full official statistical dataset provides an overall assessment of the match figures and patterns of operation of the Prüm system for DNA exchange. These figures and patterns are analysed in terms of the differentiated contributions by participating EU Member States. The data suggest a trend for West and Central European countries to concentrate the majority of Prüm matches, while DNA databases of Eastern European countries tend to contribute with profiles of people that match stains in other countries. In view of the necessary transparency and accountability of the Prüm system, more extensive and informative statistics would be an important contribution to the assessment of its functioning and societal benefits. Highlights: Analysis of a full dataset of 5 year statistics of the Prüm exchange of DNA data Total match volume and several comparative ratios are examined. Higher volume of reported DNA matches concentrates in West and Central European countries. Argument for the need of extensive and informative statistics on Prüm DNA exchange